2012
DOI: 10.1371/journal.ppat.1002743
|View full text |Cite
|
Sign up to set email alerts
|

The Salmonella Deubiquitinase SseL Inhibits Selective Autophagy of Cytosolic Aggregates

Abstract: Cell stress and infection promote the formation of ubiquitinated aggregates in both non-immune and immune cells. These structures are recognised by the autophagy receptor p62/sequestosome 1 and are substrates for selective autophagy. The intracellular growth of Salmonella enterica occurs in a membranous compartment, the Salmonella-containing vacuole (SCV), and is dependent on effectors translocated to the host cytoplasm by the Salmonella pathogenicity island-2 (SPI-2) encoded type III secretion system (T3SS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 68 publications
(121 reference statements)
1
121
0
Order By: Relevance
“…The requirement of MT dynamics for formation of the LGP C aggregate provides in our opinion a strong evidence for differentiating this aggresome from the ALIS structures that are reported by Mesquita et al in epithelial cells infected with S. Typhimurium. 59 We also confirmed that incubation of fibroblasts with an extract of heat-killed bacteria (which contains lipopolysaccharide [LPS] and flagellin) does not trigger formation of the LGP C aggresome (Fig. S12).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The requirement of MT dynamics for formation of the LGP C aggregate provides in our opinion a strong evidence for differentiating this aggresome from the ALIS structures that are reported by Mesquita et al in epithelial cells infected with S. Typhimurium. 59 We also confirmed that incubation of fibroblasts with an extract of heat-killed bacteria (which contains lipopolysaccharide [LPS] and flagellin) does not trigger formation of the LGP C aggresome (Fig. S12).…”
Section: Discussionsupporting
confidence: 67%
“…This is in marked contrast to the formation of ALIS by S. Typhimurium in epithelial cells. 59 Live cell-imaging microscopy allowed us to uncover how the distinct compartments that interact with the autophagy machinery evolve in the S. Typhimurium-infected fibroblast. Besides the distinct structural features observed, we identified differences with epithelial cells regarding autophagy receptors, timing of the autophagy events and the pathogen functions involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…110 For example, the effector SseL is identified as a DUB and deubiquitinates the ubiquitin aggregates surrounding the SCV to help bacteria escape from autophagy. 111 Another DUB discovered in Sa. typhimurium is AvrA, which inhibits host inflammatory responses by deubiquitinating IκBα and β-catenin.…”
Section: Shigella Flexnerimentioning
confidence: 99%
“…The catalytic activity of YopJ ultimately leads to the inhibition of innate and adaptive immunity responses and induction of cell death (Mukherjee et al, 2007;Paquette et al, 2012;Orth, 2002;Viboud & Bliska, 2005). In addition, S. Typhimurium produces a deubiquitinase, SseL, which functions by using a His-Asn-Cys triad to remove Lys63-linked ubiquitin chains from SCV-associated aggregates that are targeted for autophagic degradation (Mesquita et al, 2012;Rytkö nen et al, 2007). In this manner, SseL decreases the autophagic flux within the host, consequently contributing to down-modulation of NF-B-dependent cytokine production and macrophage-delayed cytotoxicity (Mesquita et al, 2012;Rytkö nen et al, 2007;Le Negrate et al, 2008).…”
Section: Gtge Is a Cysteine Proteasementioning
confidence: 99%